Bronchoconstriction following nebulised colistin in cystic fibrosis. Issue 5 (1st May 2001) - Cunningham, S; Prasad, A; Collyer, L; Carr, S; Lynn, I Balfour; Wallis, C
Abstract : Nebulised colistin is regularly used as antipseudomonal therapy in children with cystic fibrosis. We assessed bronchoconstriction in response to nebulised colistin in 58 children. Nebulised colistin significantly reduced FEV1, MEF25%, and Sao 2 for 15 minutes. In 20 children the reduction was greater than 10% from baseline FEV1, and was still at that level in five at 30 minutes. Subjective assessment, baseline FEV1, and serum IgE were unable to identify susceptible children. It is recommended that children receiving colistin should be carefully assessed for bronchoconstriction.